2009
DOI: 10.1002/rob.20303
|View full text |Cite
|
Sign up to set email alerts
|

Path‐following algorithms and experiments for an unmanned surface vehicle

Abstract: This paper addresses the problem of path-following in two-dimensional space for underactuated unmanned surface vehicles (USVs), defining a set of guidance laws at kinematic level. The proposed nonlinear Lyapunov-based control law yields convergence of the path following error coordinates to zero. Furthermore, the introduction of a virtual controlled degree of freedom for the target to be followed on the path removes singularity behaviors present in other guidance algorithms proposed in the literature. Some heu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 34 publications
1
84
0
Order By: Relevance
“…Following the analysis carried out in [6], the kinematic equations have to be rewritten keeping into account the path velocity:…”
Section: Circle-following Guidancementioning
confidence: 99%
“…Following the analysis carried out in [6], the kinematic equations have to be rewritten keeping into account the path velocity:…”
Section: Circle-following Guidancementioning
confidence: 99%
“…Path following for nonholonomic and underactuated vehicles [Bibuli et al, 2009, Sordalen and Canudas de Wit, 1993, Soetanto et al, 2003, Micaelli and Samson, 1993, Aircardi et al, 2001] provides convergence to curves in space, though not necessarily convergence to a time-parameterized trajectory. Trajectory tracking controllers drive the full state of a system to a desired time-varying reference state.…”
Section: Trajectory Trackingmentioning
confidence: 99%
“…1, operate in open environments and handle many tasks, such as station keeping [17], path following [1], or environmental monitoring [7,8]. Those researches demonstrated that a low precision two-dimensional (2D) state estimation based on GPS and compass measurements is sufficient for such applications.…”
Section: Introductionmentioning
confidence: 99%